Imaging of Neuronal and Mixed Glioneuronal Tumors. Issue 3 (May 2020) - Abdel Razek, Ahmed Abdel Khalek; Elsebaie, Nermeen A.; Zamora, Carlos; Castillo, Mauricio
Abstract : Abstract: Neuronal and mixed glioneuronal tumors represent a group of neoplasms with varying degrees of neural and glial elements. Their age of presentation varies, but they are most commonly seen in children and young adults. With the exception of anaplastic ganglioglioma and other atypical variants, most lesions are low grade; however, they can have significant morbidity because of seizures, mass effect, or difficult to treat hydrocephalus. Although many tumors show overlapping clinical and imaging features, some have relatively distinctive imaging characteristics that may aid in narrowing the differential diagnosis. In this review, we discuss relevant clinical and pathologic characteristics of these tumors and provide an overview of conventional and advanced imaging features that provide clues as to the diagnosis.